Applying an ecosystem for the Development of Scientists, Sciences, and Sovereign Knowledge to a National case - Al-Abduljabbar, AbdulHamid AbdulRahman; Al-Saud, Bandar Abdullah (Journal of engineering sciences and information technology, 2024)
This paper proposes a comprehensive roadmap to apply a sustainable national ecosystem which was introduced in a previously published work, to produce scientists, sciences, and sovereign knowledge. It begins with a background review of some regional countries history and efforts in promoting and growing sciences and scientists, to produce and own sovereign knowledge, as well as glimpses about the growing international intrests in applying and including such efforts in its national policies and development plans.Then it focuses on the relation of “scientists and sciences” ecosystem with education and entrepreneurship ecosystems, and its role in complementing them. A detailed proposed implementation plan of the ecosystem for specific national case is introduced through four dimensions that cover different elements; Enablers, Tools, Human, and Content. The first two dimentions represent the inputs domain, while the other two represent the output domain. Then eleven practical initiatives that form a basis to activate the national ecosystem are proposed to achieve necessary conditions to establish and sustain an environment which cultivate and stimulate excellence and scientific superiority, as well as, induce a critical mass of enabled scientists, who have all necessary capabilities and passion to produce new scientific theories, knowledge, and breakthroughs that enrich science and knowledge at large, thus, strengthen sovereignty and advance competitiveness and civilizations. Although this work focuses on one country as an example, its ingredients can be generalized and extended to other arab countries.
Keywords: Sovereign Knowledge; Science; Education; Making of Scientists; Sustainable Development; Eco-system